Peningkatan Kapasitas dan Penguatan Sistem Pelaporan Juru Pemantau Jentik Dalam Penerapan “1 Rumah 1 Jumantik” di Komunitas: Era Adaptasi Baru Covid-19 - Kusumaratna, Rina Kurniasri; Alam, Mohammad Nahdiyin Mangku; Supriyadi, Anisah; Suriyani , Suriyani (Universitas Nusantara PGRI Kediri, 2023)
Environmental health is an essential part of public health efforts. Interaction between humans and the environment could influence each other. One of the impacts has the emergence of health problems related to vectors, one of the vectors of the disease is known as mosquitoes. The purpose of the service is to increase capacity and strengthen the reporting system in applying the concept of